Geostatistics of the Borden Aquifer: High‐Resolution Characterization Using Direct Groundwater Velocity Measurements. Issue 3 (24th March 2022) - Osorno, T. C.; Devlin, J. F.; Bohling, G. C.
Abstract: In 1986, a seminal data set from the Canadian Forces Base (C.F.B.) Borden aquifer, Ontario, Canada, was published, illustrating, in unprecedented detail, the spatial distribution of hydraulic conductivity ( K ). Among many contributions attached to that data set was a geostatistical examination of field‐based data for comparison with theoretical predictions of macro‐dispersivity. However, that work treated K as a static parameter and the sole source of flow variability. Here, point velocity probes (PVPs) are used to extend the earlier work by collecting a novel high‐resolution data set of groundwater velocity ( v ) measurements in the C.F.B. Borden aquifer. Velocity is a dynamic parameter of fundamental importance, closely tied to solute dispersion. Over 400 velocity measurements were collected along a transect perpendicular to flow, analyzed geostatistically, and compared with the analysis of the B‐B′ cross‐section of K reported by Sudicky (1986), https://doi.org/10.1029/wr022i013p02069 . The PVP measurements exhibited geostatistics similar to those previously estimated by Sudicky (1986), https://doi.org/10.1029/wr022i013p02069 . This finding suggests, as implicitly assumed in the previous work, the distribution of v is primarily controlled by K . PVPs also provided a novel, high‐resolution data set of groundwater flow directions. Since the ultimate objective of aquifer characterization includes the definition of velocity fields, this work not only extends the 1986 work, but also demonstrates a viable alternative for characterizing flow patterns in aquifers—with the advantage that direct v measurements reflect variability in porosity and hydraulic gradient, as well as K . This could ultimately be advantageous at sites with greater heterogeneity or other dynamic hydrogeological variabilities more pronounced than those at the Borden site. Plain Language Summary: Transport of contaminants in the ground is dominated by groundwater flow. This is typically investigated using conventional methods based on water‐level measurements and other indirect techniques. This article outlines an alternative method for investigating groundwater flow by direct measurements of groundwater velocity. A chief advantage of the approach is a reduction of measurement uncertainty. Geostatistics describing aquifer structure based on the two methods were shown to be similar. This illustrates the advantages of making direct velocity measurements are not offset by a loss of data quality or geostatistical value. This new method may have application in the characterization and monitoring of contaminants transporting by groundwater or undergoing clean‐up efforts. Key Points: Geostatistics of direct groundwater velocity measurements are consistent with those from hydraulic conductivity at Canadian Forces Base Borden Correlation lengths of groundwater velocity magnitude and direction shown to be similar High‐resolution velocity data set shows plume spreading (i.e., dispersion), without Fickian dispersion, based solely on advective processes